(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article talks about an effective method of teaching football elements to schoolchildren, that is, to children under 12 years old. Advice and instructions were given on what to pay more attention to when teaching football to children and how to organize training sessions.